2015
DOI: 10.1016/j.adolescence.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of additional psychosocial intervention in reducing low birth weight and preterm birth in teenage pregnancy: A systematic review and meta‐analysis

Abstract: This systematic review aimed to assess the efficacy of psychosocial interventions in reducing risk of low birth weight (LBW) and preterm birth (PTB) in teenage pregnancy. Relevant studies were identified from Medline, Scopus, CINAHL, and CENTRAL databases. Randomized controlled trials investigating effect of psychosocial interventions on risk of LBW and PTB, compared to routine antenatal care (ANC) were eligible. Relative risks (RR) of LBW and PTB were pooled using inverse variance method. Mean differences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…When fixed-effect and random-effect results were both reported in a meta-analysis, we present random effects because it assumes that the true effects are normally distributed (Borenstein et al, 2009). Sukhato et al (2015) analyzed four birth outcomes across five randomized trials (RCTs) testing the effects of psychosocial interventions. These outcomes included low birth weight, preterm birth, mean birth weight, and mean gestational age at delivery for women less than 21 years of age.…”
Section: Overview Of Meta-analysesmentioning
confidence: 99%
“…When fixed-effect and random-effect results were both reported in a meta-analysis, we present random effects because it assumes that the true effects are normally distributed (Borenstein et al, 2009). Sukhato et al (2015) analyzed four birth outcomes across five randomized trials (RCTs) testing the effects of psychosocial interventions. These outcomes included low birth weight, preterm birth, mean birth weight, and mean gestational age at delivery for women less than 21 years of age.…”
Section: Overview Of Meta-analysesmentioning
confidence: 99%
“…In 2013, the National Center for Health Statistics reported that the U.S. preterm birth rate was 11.4% (HP 2020). A number of factors predict vulnerability to preterm births; these include young maternal age, high school education only and being a single mother, maternal history of being born preterm, maternal diabetes mellitus, maternal stress and depression, substance use, and intimate partner violence (Alhusen et al, 2014;Boivin et al, 2015;Dorfman, Srinath, Rockhill, & Hogue, 2015;Janisse, Bailey, Ager, & Sokol, 2014;Sukhato et al, 2015).…”
Section: Adverse Birth Outcomes and Their Consequencesmentioning
confidence: 99%
“…En Fortin-Langelier et al, (2019) se encuentra una relación entre la infancia, el abuso sexual y el embarazo adolescente. En Sukhato et al, (2015) se realiza un análisis de la intervención para que los niños de las adolescentes embarazadas nazcan con mejor peso. En Lohan et al, (2014) se realiza una intervención educativa basada en películas para evitar el embarazo en adolescentes.…”
Section: Introductionunclassified